2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1616968
|View full text |Cite
|
Sign up to set email alerts
|

On Spectral Analysis of Heart Rate Variability during Very Slow Yogic Breathing

Abstract: Abstract-Very slow yogic breathing techniques provide valuable insights into mechanisms of autonomous nervous system regulation that are usually not available for human subjects. This paper presents results of eight sessions of Nadi Shodhana Pranayama practiced at rate of one breath per minute. We characterized statistic and spectral measures of heart rate variability before, during, and after exercises. Significant changes include increase of VLF frequencies caused by slow breathing and decrease in average in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Though originally designed as a way to quiet the mind, these breathing techniques have also shown health benefits, especially in the area of mind-body illness. [4][5][6][7][8][9][10][11][12][13][14][15][16] Studies have suggested that pranayama practices create a relaxed state by enhancing parasympathetic tone. 11,13,16 Several studies have investigated the efficacy of a multimodality yoga intervention, which includes breathing, postures, and/or meditation, in a population of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Though originally designed as a way to quiet the mind, these breathing techniques have also shown health benefits, especially in the area of mind-body illness. [4][5][6][7][8][9][10][11][12][13][14][15][16] Studies have suggested that pranayama practices create a relaxed state by enhancing parasympathetic tone. 11,13,16 Several studies have investigated the efficacy of a multimodality yoga intervention, which includes breathing, postures, and/or meditation, in a population of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For the HRV analysis we restricted ourselves to the time domain analysis only. Study [17] has found changes in relative very low frequency (VLF) power before and during exercise. Spectral domain features can also be calculated by the toolbox we are using, but we restricted this analysis to time domain analysis as the goal is not to compare different metrices in the three different meditation techniques.…”
Section: Resultsmentioning
confidence: 99%
“…(2005) emphasized the sympathetic nervous system dynamics to counter mental stress and other external or internal disturbances effecting visceral homeostasis [5]. Jovanov E. (2005) during very slow yogic breathing found increased VLF frequencies, respiratory sinus arrhythmia, LF/HF ratio and decreased breathing frequency after exercise in comparison to state before exercise [6]. Patil S. and Telles S. (2006) in their study on two yogic based relaxation effects on HRV in cyclic meditation (CM) and supine rest (SR), showed decrease in LF power and LF/HF ratio during and after CM, whereas HF power decreased.…”
Section: Introductionmentioning
confidence: 99%